Accounting for data heterogeneity in patterns of biodiversity: an application of linear mixed effect models to the oceanic island biogeography of spore‐producing plants. Issue 8 (24th January 2013) - Patiño, Jairo; Guilhaumon, François; Whittaker, Robert J.; Triantis, Kostas A.; Gradstein, S. Robbert; Hedenäs, Lars; González‐Mancebo, Juana M.; Vanderpoorten, Alain
<x xml:space="preserve">Abstract</x> The general dynamic model of oceanic island biogeography describes the evolution of species diversity properties, including species richness (SR), through time. We investigate the hypothesis that SR in organisms with high dispersal capacities is better predicted by island area and elevation (as a surrogate of habitat diversity) than by time elapsed since island emergence and geographic isolation. Linear mixed effect models (LMMs) subjected to information theoretic model selection were employed to describe moss and liverwort SR patterns from 67 oceanic islands across 12 archipelagos. Random effects, which are used to modulate model parameters to take differences among archipelagos into account, included only a random intercept in the best‐fit model for liverworts and in one of the two best‐fit models for mosses. In this case, the other coefficients are constant across archipelagos, and we interpret the intercept as a measure of the intrinsic carrying capacity of islands within each archipelago, independently of their size, age, elevation and geographic isolation. The contribution of area and elevation to the models was substantially higher than that of time, with the least contribution made by measures of geographic isolation. This reinforces the idea that oceanic barriers are not a major impediment for migration in bryophytes and, together with the almost complete absence of in situ insular diversification, explains the comparatively limited importance of time in the models. We hence suggest that time per se has little independent role in explaining bryophyte SR and principally features as a variable accounting for the changing area and topographic complexity during the life‐cycle of oceanic islands. Simple area models reflecting habitat availability and diversity might hence prevail over more complex temporal models reflecting in‐situ speciation and dispersal (time, geographic connectivity) in explaining patterns of biodiversity for exceptionally mobile organisms.